Model checking software : 23rd International Symposium, SPIN 2016, co-located with ETAPS 2016, Eindhoven, The Netherlands, April 7-8, 2016, Proceedings /: 23rd International Symposium, SPIN 2016, co-located with ETAPS 2016, Eindhoven, The Netherlands, April 7-8, 2016, Proceedings. (2016) - Unknown
No abstract available